Treatment outcome of thyroidectomies performed under local anesthesia for nodular goiter patients attending at Banadir Hospital in Mogadishu Somalia - Olow, Mohamed Abdi Shire; Sönmez, Recep Erçin; Hassan, Mohamed Yusuf; Fıqı, Abdurrahman Osman; Alimoğlu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: Thyroidectomy; which involves the removal of total or part of the thyroid glandis a routinely performed surgery that may have perioperative risks and complications which can be life-threatening. Objective: Main objective of this study is to determine the incidence of postthyroidectomy complications at Banadir Hospital, and to put forward the clinical benefits of those which had been performed under local anesthesia. Materials and Methods: Present study; which is prospective in nature, was conducted on 25 patients between 18 and 70 years of age who were scheduled to undergo elective thyroidectomy beginning from May to July, 2017. Blood samples for calcium, albumin, thyroid hormone levels were collected pre-operatively; within 48 hours and 5 days post-operatively. Relevant data had been achieved from the medical achieve of the department. Results: Patients between 20 and 40 years of age occupied the highest percentage of population in the study. Two (8%) patients had records of previous thyroid surgery. Ultrasonographic (USG) evaluations revealed benign thyroid nodule for 23 (92%) patients, as 2 (8%) other patients were confirmed as malignancy on their fine needle aspiration cytology (FNAC) which had suspicious findings on ultrasonographic (USG) evaluations. 21 (84%) patients had pain as the chief complaint. 19(76%) patient operations had been performed under local anesthesia, while 6(24%) patients had undergone operations undergeneral anesthesia. Total thyroidectomy was performed for 10 (40%) patients, whereas the rest (n=15 (60%) were performed with subtotal, near total and partial (lobectomy, nodulectomy) resections. No permanent hypocalcemia was recorded during the postoperative period, though 2 (8%) patients had transient hoarseness due to laryngeal nerve injury and another 2 (8%) patients had findings of surgical site infections. Conclusion: Thyroidectomy procedure could end up with undesired outcomes like nerve paralysis or hypocalcemia even at most experienced hands. Considering that, definite and precise operation should be performed at once to prevent re-operations that could increase the rate of morbidity. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 222-225